Reformasi Peraturan Investasi di Indonesia - Marulak Pardede (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2023)
The purpose of this research is to find answers to the problem of the existence of many statutory regulations related to investment (obesity, hyper-regulation), which are believed to be not conducive to creating competitiveness and ease of doing business in Indonesia so the government makes a policy of simplifying these various regulations into one regulation, namely the Omnibus law on the Job Creation Law. The main problem of this research is: Are the policies of the Indonesian government to improve the competitive climate and legal certainty for investing in Indonesia, in accordance with statutory provisions? This problem is divided into several sub-sub-subjects: Current investment regulation problems; Obesity, Hyper regulation, and Regulatory Reform related to Investment; Controversy and legitimacy of the Omnibus Law in the National legal system, Suing the partiality and the negative impact of the Omnibus Law on Job Creation. The research method is a juridical-normative approach, with secondary data in the form of statutory regulations, literature, journals, and the internet. Data collection techniques used is a literature study. Data analysis technique is a qualitative descriptive analysis. The results of the study showed various investment statutory regulations in Indonesia cause obesity, hyper-regulation, which can reduce investment attractiveness. To overcome this issues, the government has taken legal breakthroughs with the omnibus law system on the Job Creation Law, to be able to trigger convenience while at the same time guaranteeing legal certainty, as well as improving the investment competitiveness climate in Indonesia.